2017
DOI: 10.17221/131/2016-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Positive effects of trehalose and cysteine on ram sperm parameters

Abstract: ABSTRACT:The aim of this study was to determine the effects of trehalose and cysteine on sperm motility, viability, mitochondrial activity and acrosome integrity during liquid storage of Merino ram semen. Ejaculates were collected using artificial vaginas from five Merino rams, microscopically evaluated and pooled at 37 °C. The pooled semen samples were diluted in a Tris-based extender, including cysteine (2 mM and 4 mM), trehalose (10 mM and 25 mM) and no antioxidant (control). Diluted semen samples were kept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Nevertheless, it is worth noting that too a high concentration of l-cysteine (5 mM and 10 mM) may have a detrimental effect on chilled boar semen quality. Similarly, Gungor et al (2017) also indicated that the addition of a higher concentration of cysteine (4 mM) could maintain the ram sperm quality during chilled storage for 48 h but the sperm viability was significantly decreased at 96 h of storage when compared to 2 mM cysteine. These findings might be due to the limitation of l-cysteine uptake by spermatozoa and the amount of ROS production during the liquid preservation period (Kaeoket et al 2010b).…”
Section: Discussionmentioning
confidence: 89%
“…Nevertheless, it is worth noting that too a high concentration of l-cysteine (5 mM and 10 mM) may have a detrimental effect on chilled boar semen quality. Similarly, Gungor et al (2017) also indicated that the addition of a higher concentration of cysteine (4 mM) could maintain the ram sperm quality during chilled storage for 48 h but the sperm viability was significantly decreased at 96 h of storage when compared to 2 mM cysteine. These findings might be due to the limitation of l-cysteine uptake by spermatozoa and the amount of ROS production during the liquid preservation period (Kaeoket et al 2010b).…”
Section: Discussionmentioning
confidence: 89%
“…Research has shown that cysteine has antioxidant properties by activating existing antioxidant mediators, thanks to its thiol group. Previous studies have demonstrated that adding cysteine to freezing media or semen extenders significantly enhanced the post‐thaw motility, viability, membrane integrity, and acrosome integrity of ram spermatozoa (Altomare et al, 2020; Çoyan et al, 2011; Gungor et al, 2017; Khalili et al, 2010). Additionally, the inclusion of cysteine in semen extenders has been found to improve individual motility and plasma membrane integrity, and significantly reduce the mitochondrial apoptosis occurrence and DNA fragmentation in Awassi ram semen (Saieed et al, 2019).…”
Section: Non‐enzymatic Antioxidantmentioning
confidence: 99%